2015
DOI: 10.1177/0038038514562852
|View full text |Cite
|
Sign up to set email alerts
|

‘Charlie Is So Cool Like’: Authenticity, Popularity and Inclusive Masculinity on YouTube

Abstract: On the world's most utilised video-sharing social networking site, YouTube, CharlieMcDonnell (Charlieissocoollike), Dan Howell (Danisnotonfire), and Jack and Finn Harries (JacksGap) are Britain's most popular video-bloggers (vloggers). With more than two million regular subscribers to each of their channels, along with millions of casual viewers, they represent a new form of authentic online celebrity. These young men, whose YouTube careers began as teenagers, do not espouse a traditional form of masculinity; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 54 publications
2
80
0
2
Order By: Relevance
“…th Century literature on adolescent males, in the 21 st Century, young men have a greater social entitlement to express themselves through a diverse spectrum of behaviors and emotions that would have previously socially coded them as gay (Anderson 2014 (Morris and Anderson 2015;Scoats 2015). Young men in these forums align themselves away from orthodox tropes of masculinity and are less concerned about whether others perceive them to be gay, straight; masculine, or feminine (White and Hobson 2015).…”
Section: Contrasting 20mentioning
confidence: 99%
“…th Century literature on adolescent males, in the 21 st Century, young men have a greater social entitlement to express themselves through a diverse spectrum of behaviors and emotions that would have previously socially coded them as gay (Anderson 2014 (Morris and Anderson 2015;Scoats 2015). Young men in these forums align themselves away from orthodox tropes of masculinity and are less concerned about whether others perceive them to be gay, straight; masculine, or feminine (White and Hobson 2015).…”
Section: Contrasting 20mentioning
confidence: 99%
“…Social networking sites such as Facebook have also contributed to this visibility, allowing users to publicly come out, state their relationship status, and whether they are "interested in" men, women, or both. Morris and Anderson (2015) also found that the most popular male YouTube celebrities in the U.K.…”
Section: Understanding Decreasing Homophobiamentioning
confidence: 80%
“…Videoblogs are asynchronous (Frobenius, 2014), meaning they do not enable immediate interaction with the audience, unlike video conferencing. Yet, the presenter on the video is able to establish a conversational and interactional mood by addressing the viewers directly, often as peers, (Frobenius, 2014) and by practicing self-disclosure and ingratiation (Griffith and Papacharissi, 2010;Morris and Anderson, 2015). This affords managers, even high up in the organization hierarchy, the opportunity to present as employees' peers.…”
Section: Researching Videoblogs and Videobloggingmentioning
confidence: 99%